1998
DOI: 10.2337/diabetes.47.8.1199
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged survival of rat islet and skin xenografts in mice treated with donor splenocytes and anti-CD154 monoclonal antibody

Abstract: Treatment of C57BL/6 mice with one transfusion of BALB/c spleen cells and a brief course of anti-CD154(anti-CD40 ligand) antibody permits BALB/c islet grafts to survive indefinitely and BALB/c skin grafts to survive for ~50 days without further intervention. We now report adaptation of this protocol to the transplantation of islet and skin xenografts. We observed prolonged survival of rat islet xenografts in mice treated with donor-specific spleen cell transfusion and anti-CD154 monoclonal antibody (mAb). Chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…The results of graft survival in Ja18 null mice in this study are consistent with our previously reported differences in islet vs. skin xenograft survival [2,3]. We report here that NKT cells are not required for islet xenograft survival, but are required to promote durable skin xenograft survival.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of graft survival in Ja18 null mice in this study are consistent with our previously reported differences in islet vs. skin xenograft survival [2,3]. We report here that NKT cells are not required for islet xenograft survival, but are required to promote durable skin xenograft survival.…”
Section: Discussionsupporting
confidence: 93%
“…In order to understand the requirements for this induction, we studied cellular elements that may contribute to xenograft survival. We found that the induction of xenograft survival is similarly effective in both thymectomized and in euthymic mice [2]. Additional studies demonstrated that the elimination of CD4 + cells but not CD8 + cells enhances xenograft survival [3].…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Co-stimulation blockade induces prolonged but not permanent skin allograft and xenograft survival [24,[30][31][32]. In contrast, islet allograft and xenografts can survive permanently in mice treated with co-stimulation blockade [25,30,31].…”
Section: Islet Xenografts Survive Long Term In Xenogeneic Chimeric Micementioning
confidence: 99%
“…Dosing regimens were based on results from other reports in the literature. 9,[13][14][15] Each transplant recipient was assigned a coded number, and those caring for the animals, measuring outcomes, and analyzing samples were blinded to the treatment group. The Animal Ethics Committee stipulated that surviving animals be killed on or before day 8 if they showed signs of impending liver failure (Ͼ20% loss in weight, reduced activity, or bilirubin Ͼ 200 IU/L).…”
Section: Experimental Designmentioning
confidence: 99%